2021
DOI: 10.1024/2673-8627/a000003
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Psychologists in Healthcare During the COVID-19 Pandemic

Abstract: Abstract. Introduction: The COVID-19 pandemic has impacted individuals, communities, and whole populations. Experts across many different fields contributed their time and efforts in different ways to respond to the pandemic. Psychologists working in healthcare provided support and led many initiatives, both regionally and nationally. However, it is unknown how this has differed across Europe and its full range of activities and contributions. Aim: The current study is a survey of European member associations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…This was commonly seen across psychology during the pandemic [49]. This is not a sustainable model and funding for rapid consensus approaches should be considered and made available in the future; a call to action made both by this group [41] and others [50]. Financial resourcing is also likely to speed up processes further, as those involved voluntarily could dedicate more time if the role was part of paid work.…”
Section: Challengesmentioning
confidence: 99%
“…This was commonly seen across psychology during the pandemic [49]. This is not a sustainable model and funding for rapid consensus approaches should be considered and made available in the future; a call to action made both by this group [41] and others [50]. Financial resourcing is also likely to speed up processes further, as those involved voluntarily could dedicate more time if the role was part of paid work.…”
Section: Challengesmentioning
confidence: 99%
“…A study from the UK found that 86% of parents of autistic children felt a lack of government support during lockdown with 70% reporting that their daily routines were still significantly different since the pandemic began (Pavlopoulou et al , 2020). While many countries dealt with the pandemic in their own way, there were however criticisms of some countries who did not have adequate representation from mental health experts on COVID-19 advisory panels at the very beginning of the pandemic (Karekla et al , 2021; O'Connor et al , 2021). Notably, the initial contribution of mental health science was lessened relative to other areas of expertise such as virology and epidemiology; however, as the pandemic continued the mental health implications were becoming increasingly apparent.…”
Section: Discussionmentioning
confidence: 99%
“…Many governments have increased mental health funding in the wake of the pandemic; however, more sufficient investment is needed (Latoo et al , 2021). Furthermore, research advocates for mental health experts such as psychologists as integral partners in response teams when dealing with problems with a demonstrable behavioural component, either in their emergency or in their intervention phases (Karekla et al , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Although psychological expertise has been integrated into several national policies and action plans [ 13 ], very few studies have specifically investigated the effect of the pandemic on psychologists themselves (e.g., [ 14 ]). Among these studies, the position of psychologists in supporting the medical system [ 15 ] and in responding to the COVID-19 pandemic through research, practice, education, and advocacy [ 16 ] has nevertheless been widely recognised.…”
Section: Introductionmentioning
confidence: 99%